Behavior management in physical education : a practical guide - Alstot, Andrew E.; Alstot, Crystal D. (Abingdon, Oxon ; New York, NY : Routledge, 2019)
"Behavior Management in Physical Education provides evidence-based, practical guidance on behavior management in the physical education classroom. Readers will learn how to identify and define problem behavior, discover the reasons behind misbehavior, create thriving classrooms via the incorporation of positive and proactive classroom management strategies, implement procedures to address problem behavior, and collect appropriate data to ensure interventions are having a meaningful impact"--
An introduction to behavior management in physical education -- Preparing for success: proactive behavior management strategies -- Reasons why students misbehave -- When students misbehave: reactive behavior management strategies -- Data collection and analysis -- Self-management and ethics.
OCLC-licensed vendor bibliographic record.
Keywords: Physical education and training -- Study and teaching -- Psychological aspects; Problem children -- Behavior modification; Classroom management; HEALTH & FITNESS / Healthy Living; HEALTH & FITNESS / Holism; HEALTH & FITNESS / Reference; MEDICAL / Preventive Medicine